Propuesta de un sistema de control interno de los servicios académicos estudiantiles de la UTMACH. - Pacheco Quizhpe, Sandra Esperanza (My University, 2018)
This project documents the process related to the development of a proposal in the automation of academic processes through the use of ICTs, in the strategic competencies of the Technical University of Machala, the objective is to analyze which processes can be developed through of the new communication and information technologies, improve the quality of the service to the procedures related to the students and teaching, with the intention of mitigating the discontent that causes tedious institutional procedures that can be optimized in the computer system of the educational institution; The methodology used is the deductive-inductive method that allows integrating the compilation of both theoretical and field data that lead to an understanding of the problem. The theoretical foundation is based on a macro, meso and micro approach to the conceptual incidents observed in the aforementioned research; in the final part, the results are postulated where it is detailed which processes can be automated, in what way, to what extent they are automatable and infer their repercussions on the liking of the student body.
El presente proyecto documenta el proceso afín a la elaboración de una propuesta en la automatización de procesos académicos mediante el uso de las TIC´s, en las competencias estratégicas de la Universidad Técnica de Machala, el objetivo es analizar cuales procesos pueden ser gestados a través de las nuevas tecnologías de comunicación e información, mejorar la calidad del servicio a los procedimientos relacionados a los estudiantes y docencia, con la intención de mitigar el descontento que origina trámites institucionales tediosos que bien pueden ser optimizados en el sistema informático de la entidad educativa; la metodología empleada es la deductiva-inductiva que permite integrar la compilación de datos tanto teóricos como de campo que derivan en la comprensión de la problemática. La fundamentación teórica se basa en un enfoque a nivel macro, meso y micro de las incidencias conceptuales observadas en las investigaciones citadas; en la parte final se postulan los resultados donde se detalla cuáles procesos pueden ser automatizados, en qué manera, hasta qué grado son automatizables e inferir sus repercusiones sobre el agrado del cuerpo estudiantil.
Keywords: AUTOMATIZACIÓN; PROCESOS; ACADÉMICOS